Proportion of medical admissions that may be hospitalised at home and their service utilisation patterns: a single-centre, descriptive retrospective cohort study in Singapore - John T Y Soong; Stephanie Q Ko; Zhemin Wang; Samuel Li Earn Goh (BMJ Open, 2023)
Objectives For eligible patient groups, hospital-at-home (HaH) programmes have been shown to deliver equivalent patient outcomes with cost reduction compared with standard care. This study aims to establish a benchmark of inpatient admissions that could potentially be substituted by HaH services.Design Descriptive retrospective cohort study.Setting Academic tertiary hospital in Singapore.Participants 124 253 medical admissions over 20 months (January 2016 to August 2017).Primary and secondary outcome measures The primary measure was the proportion of hospitalised patients who may be eligible for HaH, based on eligibility criteria adapted for the Singapore context. The secondary measures were the utilisation patterns and outcomes of these patients.Results Applying generalised eligibility criteria to the retrospective dataset showed that 53.0% of 124 253 medical admissions fitted the eligibility criteria for HaH based on administrative data. 46.8% of such patients had a length of stay <48 hours (‘short-stay’) and 53.1% had a length of stay ≥48 hours (‘medium-stay’). The mortality rate and the 30-day readmission rate were lower in the ‘short-stay’ cohort (0.6%, 12.8%) compared with the ‘medium-stay’ cohort (0.7%, 20.3%). The key services used by both groups were: parenteral drug administration, blood investigations, imaging procedures and consultations with allied health professionals.Conclusions Up to 53.0% of medical admissions receive care elements that HaH programmes could provide. Applying estimates of functional limitations and patient preferences, we propose a target of ~18% of inpatient medical admissions to be substituted by HaH services. The methodology adopted in this paper is a reproducible approach to characterise potential patients and service utilisation requirements when developing such programmes.